Cortical Visual Impairments and Learning Disabilities - Chokron, Sylvie; Kovarski, Klara; Dutton, Gordon N. (Frontiers in Human Neuroscience, 2021)
Medical advances in neonatology have improved the survival rate of premature infants, as well as children who are born in difficult neurological conditions. As a result, the prevalence of cerebral dysfunctions, whether minimal or more severe, is increasing in all industrialized countries and in some developing nations. Whereas in the past, ophthalmological diseases were considered as being principally responsible for severe visual impairment, today, all recent epidemiological studies show that the primary cause of blindness and severe visual impairment in children in industrialized countries is now neurological in origin. Neurological lesions acquired around the time of birth currently comprise the commonest cause of damage to the visual system. Cerebral Visual Impairments (CVI) have long been ignored, or have been confused either with other ophthalmological disorders causing low vision, or with a range of learning disabilities. We present here the deleterious consequences that CVI can have upon learning and social interaction, and how these can be accorded behavioral labels without the underlying visual causes being considered. We discuss the need to train and inform clinicians in the identification and diagnosis of CVI, and how to distinguish the diagnosis of CVI from amongst other visual disorders, and the specific learning disorders. This is important because the range of strategies needed to enhance the development of children with CVI is specific to each child’s unique visual needs, rendering incorrect labelling or diagnosis potentially detrimental to affected children.